Transition from pediatric to adult nephropathic cystinosis care: the structure, challenges and lessons learned - Borsheim, Brianna; Vissing, Andrew; Ghossein, Cybele (Frontiers in Pediatrics, 2025)
Cystinosis is a rare, autosomal recessive disorder that results in a build up of the amino acid cystine in the body ( 1). With early diagnosis and advances in patient prognosis over the years, this has led to an increasing number of adolescents and adults with cystinosis. Multiple studies have shown that adolescents and young adults (YA) with kidney disease transitioning to adult care are at high risk for poor health outcomes ( 1– 4). In addition, patients with cystinosis have cognitive and psychosocial struggles that may interfere with their health care autonomy. Pediatric and adult nephrologists often act as the care-quarterback for patients with cystinosis at the time of transition. Northwestern Medicine (NM) Nephrology has implemented a formal program for the transition of care for young adults with kidney disease from Lurie Children's Hospital to Northwestern Medicine. This multidisciplinary team has assisted in the transition of several patients with nephropathic cystinosis since its inception. There are a myriad of challenges that arise as patients with cystinosis transition from pediatric to adult care including inadequate resourcing, loss of continuity and lack of adult expertise in rare pediatric diseases. While there is no universally accepted definition of transition success, the process should ensure uninterrupted care, address evolving medical needs and support patients’ autonomy and self-advocacy in adulthood.